Epistemic virtues and the historian's practices: the case of historical sensibility on Brazilian historiography (1980-1990) - Munhoz Ohara, Joao Rodolfo [UNESP] (Univ Federal Ouro Preto, Dept Historia, 2016)
What could it mean to say that one has historical sensibility? This paper investigates this question and how such sensibility was placed among the desirable values for a historian to hold and to exercise in his own professional practices. The main sources for this study are book reviews, obituaries, and homage articles published in Brazilian, history journals between 1980 and 1990. Historical sensibility, then, seems to appear in two different senses: (1) as an epistemic virtue and (2) as a meta-virtue, orienting the exercise of other virtues. This does not mean that historians properly disagreed about the meaning of historical sensibility, but rather that these two different uses refer to distinct repertoires of virtues configured around different notions of what is proper history - and, therefore, of what is a proper historian.
Keywords: Epistemic virtues; Brazilian historiography; Discourse